Controlled release of dextrin-conjugated growth factors to support growth and differentiation of neural stem cells - Elaine L. Ferguson; Sameza Naseer; Lydia C. Powell; Joseph Hardwicke; Fraser I. Young; Bangfu Zhu; Qian Liu; Bing Song; David W. Thomas (Stem Cell Research, 2018)
An essential aspect of stem cell in vitro culture and in vivo therapy is achieving sustained levels of growth factors to support stem cell survival and expansion, while maintaining their multipotency and differentiation potential. This study investigated the ability of dextrin (~74,000 g/mol; 27.8 mol% succinoylation) conjugated to epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF; or FGF-2) (3.9 and 6.7% w/w protein loading, respectively) to support the expansion and differentiation of stem cells in vitro via sustained, controllable growth factor release. Supplementation of mouse neural stem cells (mNSCs) with dextrin-growth factor conjugates led to greater and prolonged proliferation compared to unbound EGF/bFGF controls, with no detectable apoptosis after 7 days of treatment. Immunocytochemical detection of neural precursor (nestin) and differentiation (Olig2, MAP2, GFAP) markers verified that controlled release of dextrin-conjugated growth factors preserves stem cell properties of mNSCs for up to 7 days. These results show the potential of dextrin-growth factor conjugates for localized delivery of bioactive therapeutic agents to support stem cell expansion and differentiation, and as an adjunct to direct neuronal repair. Keywords: Polymer therapeutics, Biodegradable polymers, Growth factors, Neural stem cells, Controlled release